Fast ion swapping for quantum-information processing - Kaufmann, H.; Ruster, T.; Schmiegelow, C. T.; Luda, M. A.; Kaushal, V.; Schulz, J.; Von Lindenfels, D.; Schmidt-Kaler, F.; Poschinger, U. G. (Physical Review A, 2017)
We demonstrate a swap gate between laser-cooled ions in a segmented microtrap via fast physical swapping of the ion positions. This operation is used in conjunction with qubit initialization, manipulation, and readout and with other types of shuttling operations such as linear transport and crystal separation and merging. Combining these operations, we perform quantum process tomography of the swap gate, obtaining a mean process fidelity of 99.5(5)%. The swap operation is demonstrated with motional excitations below 0.05(1) quantum for all six collective modes of a two-ion crystal for a process duration of 42μs. Extending these techniques to three ions, we reverse the order of a three-ion crystal and reconstruct the truth table for this operation, resulting in a mean process fidelity of 99.96(13)% in the logical basis.
CRIS-Team Scopus Importer:2023-03-27